Menguak Hambatan dan Solusi untuk Pendidikan Berkelanjutan di Sekolah dengan Fasilitas Minim - Lili Suharningsih; Achmad Fathoni (Perspektif : Jurnal Pendidikan dan Ilmu Bahasa, 2025)
Lack of facilities in schools is one of the main challenges in realizing sustainable education in Indonesia, especially in remote and underdeveloped areas. This study aims to identify the challenges faced by schools with limited facilities and formulate solutions that can be implemented to support the sustainability of education. The research method used is qualitative with a case study approach, involving direct observation and in-depth interviews with teachers, students, and policy makers in three schools with minimal facilities. The findings show that the main obstacles include limited classroom space, limited learning tools, and difficult access to educational technology. In addition, student and teacher motivation is also influenced by these conditions. Proposed solutions include strengthening local community cooperation, optimizing government assistance funds, and implementing simple technological innovations that are appropriate to the local context. This study provides the importance of education policy, especially in the preparation of inclusive and local needs-based programs to support educational poverty in areas with limited facilities.